2017
DOI: 10.1016/j.ijheatmasstransfer.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Passive scalar diffusion in the near field region of turbulent rectangular submerged free jets

Abstract: Jets are a common way to transfer mass among fluids, or from a fluid to a surface. At moderate Reynolds numbers and low turbulent intensities the jet exhibits a Near Field Region (NFR) several diameters long. Numerical results and a theoretical model are presented for the passive scalar diffusion in the NFR of a submerged free jet. Large Eddy Simulations (LES), in the Reynolds number 5000-40,000 and the Schmidt number range 1-100, are performed obtaining the passive scalar fields. Three mathematical models for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 50 publications
(95 reference statements)
3
24
2
Order By: Relevance
“…Reynolds number from 5000 to 40,000, for a molecular Prandtl or Schmidt number, , Pr Sc , equals to 1, since the spreading of the passive scalar in the PCR and FDR is governed only by the eddy diffusivity. This work extends the 2D approach, employed in [51], showing that with the 3D approach it is possible to define a new theory for the diffusion of the passive scalar in the FDR. which is important to be used as input in the RANS modeling for computing the heat transfer in a jet impinging a single smooth cylinder [56][57][58][59][60][61][62], a finned cylinder [63][64][65][66][67], two [68,69] and three cylinders in a row [70,71].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Reynolds number from 5000 to 40,000, for a molecular Prandtl or Schmidt number, , Pr Sc , equals to 1, since the spreading of the passive scalar in the PCR and FDR is governed only by the eddy diffusivity. This work extends the 2D approach, employed in [51], showing that with the 3D approach it is possible to define a new theory for the diffusion of the passive scalar in the FDR. which is important to be used as input in the RANS modeling for computing the heat transfer in a jet impinging a single smooth cylinder [56][57][58][59][60][61][62], a finned cylinder [63][64][65][66][67], two [68,69] and three cylinders in a row [70,71].…”
Section: Introductionmentioning
confidence: 71%
“…The diffusivity of a particle is proportional to its radius, according to the Stoke-Einstein relation, [49], and the Cunningham empirical equation, [50], giving a Schmidt number of air in the range from 1 to 100 for particle radius of the order of . The diffusion of the passive scalar in turbulent planar jets has been investigated in the URF and PCR in [51], but not in the FDR, finding that the turbulent Prandtl or Schmidt number,…”
Section: Introductionmentioning
confidence: 99%
“…The new flow evolution of the jet can be important in several heat transfer applications: as a jet impinging a single smooth cylinder, [22][23][24][25][26][27][28], a finned cylinder, [29][30][31][32][33]; two cylinders in a row, [34][35]; and three cylinders in a row, [36][37]. The numerical results of [38][39][40][41][42] confirmed that the URF, as well as the NDF and SDF, are predictable numerically.…”
Section: Introductionmentioning
confidence: 85%
“…For T = 0F , some turbulence is present in the oil jet (k 1m 2 /s 2 ) but it is dissipated one pipe diameter downstream the bypass (k 10 −3 m 2 /s 2 ). For T ≥ 25F the characteristic turbulent mixing layer at the jet boundary and the potential core region, of triangular shape, at the center of the jet can be observed (Gori et al, 2012;Angelino et al, 2016;Boghi et al, 2016Boghi et al, , 2017b. For T ≥ 25F the jet bends towards the top of the pipe.…”
Section: Results At 2mm Wax Particle Diametermentioning
confidence: 97%
“…In the present study, the velocity at the center of the oil jet is about 300 times higher than the pig velocity. Despite the jet axial velocity diminishes with the increasing distance (Gori et al, 2012;Boghi et al, 2016;Angelino et al, 2016;Boghi et al, 2017b), the acceleration gained in proximity of the pig blasts the wax chips much further downstream compared to the sealing pig. This prevents the deposit from piling up in front of the pig.…”
Section: Discussionmentioning
confidence: 99%